Prevention and treatment of cancers by immune modulating nutrients. Issue 6 (9th March 2016) - Janakiram, Naveena B.; Mohammed, Altaf; Madka, Venkateshwar; Kumar, Gaurav; Rao, Chinthalapally V.
Abstract : Immune modulatory effects of dietary nutrients during tumor growth: several bioactive nutrients enhance innate immune responses by increasing natural killer and CD8 cell cytotoxicity toward inhibition of tumor growth. Nutrients levels are to be balanced to achieve immune responses to modulate the tumor growth. Bioactive components of dietary nutrients enhance anti‐inflammatory cytokines, decrease T regulatory cells, and enhance antitumor immunity. Overall dietary nutrients inhibit tumor growth, invasion, and metastases. Abstract : Epidemiological and laboratory data support the protective effects of bioactive nutrients in our diets for various diseases. Along with various factors, such as genetic history, alcohol, smoking, exercise, and dietary choices play a vital role in affecting an individual's immune responses toward a transforming cell, by either preventing or accelerating a neoplastic transformation. Ample evidence suggests that dietary nutrients control the inflammatory and protumorigenic responses in immune cells. Immunoprevention is usually associated with the modulation of immune responses that help in resolving the inflammation, thus improving clinical outcome. Various metabolic pathway‐related nutrients, including glutamine, arginine, vitamins, minerals, and long‐chain fatty acids, are important components of immunonutrient mixes. Epidemiological studies related to these substances have reported different results, with no or minimal effects. However, several studies suggest that these nutrients may have immune‐modulating effects that may lower cancer risk. Preclinical studies submit that most of these components may provide beneficial effects. The present review discusses the available data, the immune‐modulating functions of these nutrients, and how these substances could be used to study immune modulation in a neoplastic environment. Further research will help to determine whether the mechanistic signaling pathways in immune cells altered by nutrients can be exploited for cancer prevention and treatment.